2022
DOI: 10.1055/s-0042-1756165
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Male- and Female-Spoken Vowel Acoustics on Envelope-Following Responses

Abstract: The influence of male and female vowel characteristics on the envelope-following responses (EFRs) is not well understood. This study explored the role of vowel characteristics on the EFR at the fundamental frequency (f0) in response to the vowel /ε/ (as in “head”). Vowel tokens were spoken by five males and five females and EFRs were measured in 25 young adults (21 females). An auditory model was used to estimate changes in auditory processing that might account for talker effects on EFR amplitude. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This study replicated the male/female talker effects on continuous speech ABRs (Figure 1b) but also demonstrated that f0 accounted for a large portion of these ABR differences (Figure 3a). While important to confirm, this result is not surprising, given the well-known rate effects for ABRs to brief stimuli (e.g., Burkard et al, 1990;Burkard and Hecox, 1983;Don et al, 1977;Jiang et al, 2009;Polonenko and Maddox, 2022), and the lower amplitudes for talkers with higher f0s in other auditory responses using different methods with continuous speech (Canneyt et al, 2021;Easwar et al, 2021Easwar et al, , 2022Maddox and Lee, 2018;Saiz-Alía et al, 2019;Saiz-Alia and Reichenbach, 2020). What this study adds is the systematic confirmation of f0 driving much of the ABR differences by keeping the same talkers while only adjusting the f0.…”
Section: The F0 Accounted For Much Of the Talker Effects On Abrssupporting
confidence: 64%
See 2 more Smart Citations
“…This study replicated the male/female talker effects on continuous speech ABRs (Figure 1b) but also demonstrated that f0 accounted for a large portion of these ABR differences (Figure 3a). While important to confirm, this result is not surprising, given the well-known rate effects for ABRs to brief stimuli (e.g., Burkard et al, 1990;Burkard and Hecox, 1983;Don et al, 1977;Jiang et al, 2009;Polonenko and Maddox, 2022), and the lower amplitudes for talkers with higher f0s in other auditory responses using different methods with continuous speech (Canneyt et al, 2021;Easwar et al, 2021Easwar et al, , 2022Maddox and Lee, 2018;Saiz-Alía et al, 2019;Saiz-Alia and Reichenbach, 2020). What this study adds is the systematic confirmation of f0 driving much of the ABR differences by keeping the same talkers while only adjusting the f0.…”
Section: The F0 Accounted For Much Of the Talker Effects On Abrssupporting
confidence: 64%
“…Only recently have researchers been able to use such naturally dynamic speech to investigate auditory neural processing through responses derived from electroencephalography (EEG) or magnetoencephalography. With several of these different new methods, however, the responses to female talkers seem to be smaller than to male talkers (Canneyt et al, 2021;Commuri et al, 2023;Easwar et al, 2021Easwar et al, , 2022Maddox and Lee, 2018;Polonenko and Maddox, 2021;Saiz-Alía et al, 2019;Saiz-Alia and Reichenbach, 2020), which can have implications/consequences for experiments requiring multiple talkers to more closely resemble real-life scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation